1979
DOI: 10.1212/wnl.29.3.363
|View full text |Cite
|
Sign up to set email alerts
|

Bromocriptine in Parkinson disease

Abstract: Bromocriptine was administered to 66 patients with advanced Parkinson disease (PD) and increasing disability despite optimal treatment with levodopa/carbidopa (Sinemet). Forty-five patients tolerated at least 25 mg per day of bromocriptine (the "adequately treated" group) in addition to Sinemet and had significantly decreased rigidity, tremor, bradykinesia, gait disturbance, and total score, but increased involuntary movements. Twenty-five of these 45 patients improved by at least one stage. Among the 45 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

1980
1980
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…(1) Although all the signs of the disease were improved by treatment with bromo criptine plus levodopa, the effect was greatest on the on-off response and on the dyskinetic symtoms [29,30). Not all authors agree that this is so, some reporting that only the fre quency of the 'swings' is changed [22,36], Lees et al [26] on the other hand, reported that 8 patients treated with bromocriptine alone (mean dose = 80 mg daily) for 2 years were never troubled by dyskinesia.…”
Section: Discussionmentioning
confidence: 99%
“…(1) Although all the signs of the disease were improved by treatment with bromo criptine plus levodopa, the effect was greatest on the on-off response and on the dyskinetic symtoms [29,30). Not all authors agree that this is so, some reporting that only the fre quency of the 'swings' is changed [22,36], Lees et al [26] on the other hand, reported that 8 patients treated with bromocriptine alone (mean dose = 80 mg daily) for 2 years were never troubled by dyskinesia.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of BCT in patients with motor fluctuations had been reported before but was difficult to interpret because few authors specified whether the fluctuations were "wearing off" or true "on-off" (Kartzinel and Calne, 1976;Calne et al, 1978;Lieberman et al, 1979;Lieberman et al, 1980). Fahn et al (1979) clearly states that they studied patients in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…The relative effects of the newer antiparkinsonian agents on wearing off and on-off have been only partially studied. Reports on the efficacy of bromocriptine have been variable and some differences may be due to different definitions of the on-off phenomenon (Fahn et al, 1979;KartzineI and Calne, 1976;Parkes et al, 1976 b;Calne et al, 1978;Lieberman et al, 1979) as well as the fact that some studies were not specifically designed to address the particular issue of on-off. In fact, only one of the prior studies (Kartzinel and Calne, 1976) was specifically designed to evaluate BCT and this phenomenon, but the type of fluctuation was not clearly stated.…”
mentioning
confidence: 99%
“…Results have been especially good in those patients with mild to moderate disease, never treated with levodopa, who had an excellent initial response to bromocriptine (48, 64). Patients successfully treated with bromocriptine after they became unresponsive or poorly responsive to levodopa have not always done as well (48, 65, 66). In one group, only 25 percent maintained improvement for one year (65), and 14 percent for two years (66).…”
Section: Treatment Of Parkinsonismmentioning
confidence: 99%
“…Patients successfully treated with bromocriptine after they became unresponsive or poorly responsive to levodopa have not always done as well (48, 65, 66). In one group, only 25 percent maintained improvement for one year (65), and 14 percent for two years (66). In another unsegregated group of patients, 45 percent showed sustained benefits at one year, but only 12 percent after two years of treatment (67).…”
Section: Treatment Of Parkinsonismmentioning
confidence: 99%